Aqueous TMAO solution under high hydrostatic pressure. Issue 19 (11th May 2021) - Kolling, Inga; Hölzl, Christoph; Imoto, Sho; Alfarano, Serena R.; Vondracek, Hendrik; Knake, Lukas; Sebastiani, Federico; Novelli, Fabio; Hoberg, Claudius; Brubach, Jean-Blaise; Roy, Pascale; Forbert, Harald; et al.
Abstract : Aqueous TMAO solution in a diamond anvil cell pressurized up to 12 kbar shows spectral shifts in its THz extinction due to TMAO compression, increased TMAO–water coordination and a better visibility of hydration water around the hydrophobic groups. Abstract : Trimethylamine N -oxide (TMAO) is a well known osmolyte in nature, which is used by deep sea fish to stabilize proteins against High Hydrostatic Pressure (HHP). We present a combined ab initio molecular dynamics, force field molecular dynamics, and THz absorption study of TMAO in water up to 12 kbar to decipher its solvation properties upon extreme compression. On the hydrophilic oxygen side of TMAO, AIMD simulations at 1 bar and 10 kbar predict a change of the coordination number from a dominating TMAO·(H2 O)3 complex at ambient conditions towards an increased population of a TMAO·(H2 O)4 complex at HHP conditions. This increase of the TMAO–oxygen coordination number goes in line with a weakening of the local hydrogen bond network, spectroscopic shifts and intensity changes of the corresponding intermolecular THz bands. Using a pressure-dependent HHP force field, FFMD simulations predict a significant increase of hydrophobic hydration from 1 bar up to 4–5 kbar, which levels off at higher pressures up to 10 kbar. THz spectroscopic data reveal two important pressure regimes with spectroscopic inflection points of the dominant intermolecular modes: The first regime (1.5–2 kbar) is barely recognizable in the simulation data. However, it relates well with the observation that the apparent molar volume of solvated TMAO is nearly constant in the biologically relevant pressure range up to 1 kbar as found in the deepest habitats on Earth in the ocean. The second inflection point around 4–5 kbar is related to the amount of hydrophobic hydration as predicted by the FFMD simulations. In particular, the blueshift of the intramolecular CNC bending mode of TMAO at about 390 cm −1 is the spectroscopic signature of increasingly pronounced pressure-induced changes in the solvation shell of TMAO. Thus, the CNC bend can serve as local pressure sensor in the multi-kbar pressure regime.